The effects of ISO 9001 quality management system on innovation and management capacities in the Malaysian furniture sector. - Ratnasingam, Jegatheswaran; Yoon, C. Y.; Ioras, Florin (Transilvania University Press, Brasov, Romania, 2013)
Although the ISO 9001 quality management system is often perceived to be a marketing tool within the manufacturing industry, its implications on the innovation and management capacities of the furniture industry remain unknown. A survey of furniture manufacturers in Malaysia revealed that lack of innovation and ineffective management were among the main problems faced within the industry. Using a structured questionnaire, a survey of the ISO-certified manufacturers revealed that the ISO 9001 quality management system has a positive correlation on process innovation but not on product innovation. Therefore, ISO-certification would be beneficial for productivity improvement and identifying cost-cutting measures in furniture manufacturing enterprises. On the other hand, ISO-certification has a significant influence on the management of furniture enterprises, especially with regards to systematic decision-making and boosting the level of professionalism. Therefore, ISO-certification may be a useful tool to enhance the management competency and also improve the productivity within the furniture manufacturing sector.